ПІДВИЩЕННЯ ДОСТОВІРНОСТІ ДІАГНОСТУВАННЯ НАПРУГОЮ ІЗОЛЯЦІЇ ЕМАЛЬОВАНИХ ПРОВОДІВ - Євтух, П.С.; Вакуленко, О.О.; Михайлов, О.В. (Інститут електродинаміки НАН України, Київ, 2015)
The article deals with new approaches to the improvement of the certainty of diagnosing voltage insulation enameled wires by voltage and the shortcomings of standard methods are exposed. On the basis of the metrological research of statistical samples with abnormal results is determined that they are "emissions" from the normal distribution. The statistical models with the elements of robust analysis to reduce the probability of errors in assigning abnormal breakdown voltage to a distribution law in order to use them further as sources of information about the state of the enameled wire insulation defects are suggested. The advantage of the developed method of "continuous contact" at research of enamelled coating directly in the locations of indulgence and defect insulation is revealed. The construction of mathematical models based on statistical series Gram-Charlier to establish the real state of the enameled wire insulation defects is described. References 10, figures 4.